Products exchange in a multi-level distribution network - Benfriha, Abdennour -Ilyas; Triqui-Sari, Lamia; Bougloula, Aimade-Eddine (International Colloquium on Logistics and Supply Chain Management (LOGISTIQUA), 2019)
This study addresses the problem of inventory management in a multi-level retailers' network of the company Lit Mag that manufactures and distributes mattresses. Its distribution network constitutes a central warehouse and several distribution centers located in Algerian cities, and each center delivers vendors to the area and each vendor is connected to set of customers. The network studied is composed of several levels: the starting point is the warehouse, the first level of the distributors, the second level for sellers and the last level for customers. each retailer in the network handles its order locally and independently of other retailers. In this work, we propose a collaboration between the different actors of the same level, by the exchange of products between them, in order to satisfy the demand of a seller by the residual stock of another neighbor seller and this is applied to all stages of the network. The purpose of this study in to see the impact of product exchanges in the distribution networks and their influence on the total costs of the logistics chain from the central warehouse to the final customer